DEVELOPMENT OF TRADE BETWEEN UKRAINE AND THE EU IN THE CONTEXT OF EUROPEAN INTEGRATION - Власенко, Ірина; Тернова, Алла (SWorldJournal, 2025)
For our country, deepening trade relations with the EU countries is extremely important, since Ukraine has identified European integration as the path to its further development. The development of these relations contributes to attracting foreign investm